The Nature of Northern Australia - Woinarski, John; Mackey, Brendan; Nix, Henry; Traill, Barry (ANU Press, 2023)
Northern Australia stands out as one of the largest natural areas remaining on Earth- alongside such global treasures as the Amazon rainforests, the boreal conifer forests of Alaska and Canada, and the polar wilderness of Antarctica. Nature remains in abundance in 'the North.' Its intact tropical savannas, rainforests, and free flowing rivers provide a basis for much of the economic activity and the quality of life for residents of the area. The Nature of Northern Australia details the latest science on the Northern environment. With increasing debate over the future of Australia's often forgotten North, this is a timely examination of its environmental significance, the ecological processes that make it function, and the economies that are compatible with maintaining healthy communities and people and healthy country into the future. The authors, Dr. John Woinarski, Professor Brendan Mackey, Professor Henry Nix and Dr. Barry Traill, are leading experts on the environment of Northern Australia, and combined have many decades of experience on Northern ecology and land management.